Authorizing the Public Utility as a New Strategy for Preserving the Users’ Rights: Concession Contrats as a Case Study - Merah, Ahmed; Haidour, Djelloul (Journal of Legal Studies and Researches, 2020)
Authorizing the public utilities is considered as one of the main partnership strategies through which the state makes a contract with the private sector in managing, constructing and operating a public utility and exploiting it commercially for a sufficient period of time that enables it to give back the costs of this project and making gains and profits. However, the contract according to this way, requires legal and regulatory frameworks that protect the state from the dangers of the long foreign investments, and give to the investor enough guarantees which protect him the public partner privileges, and preserve the rights of users in taking profits from the public utilities services provided under the authorization of the public utilities.